2007
DOI: 10.1002/chin.200713188
|View full text |Cite
|
Sign up to set email alerts
|

Efficient ortho‐Oxidation of Phenol and Synthesis of anti‐MRSA and anti‐VRE Compound Abietaquinone Methide from Dehydroabietic Acid.

Abstract: Terpenes U 0200Efficient ortho-Oxidation of Phenol and Synthesis of anti-MRSA and anti-VRE Compound Abietaquinone Methide from Dehydroabietic Acid. -A method is developed for the ortho-oxidation of phenols using m-chlorobenzoyl peroxide which is prepared from m-chloroperbenzoic acid. The method is applied to the synthesis of abietaquinone methide (VII) from ferruginol (VI). -(TADA*, M.; ISHIMARU, K.; Chem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…aureus , and vancomycin‐sensible and vancomycin‐resistant Enterococcus species was investigated. A previous assay showed that all derivatives ( 2–12 ) were inactive toward Gram‐negative bacteria (MIC values >125 µg/mL), including Escherichia coli (ATCC 25922) and Pseudomonas aeruginosa (ATCC 27853), in agreement with former observations (Gaspar‐Marques et al ., ; Tada and Ishimaru, ; Yang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…aureus , and vancomycin‐sensible and vancomycin‐resistant Enterococcus species was investigated. A previous assay showed that all derivatives ( 2–12 ) were inactive toward Gram‐negative bacteria (MIC values >125 µg/mL), including Escherichia coli (ATCC 25922) and Pseudomonas aeruginosa (ATCC 27853), in agreement with former observations (Gaspar‐Marques et al ., ; Tada and Ishimaru, ; Yang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…) should cross the membrane system of bacteria (a ΔpH potential driven process) and, within the cytoplasm, should inhibit protein biosynthesis by interaction of the hydrated horminone‐Mg 2+ complex with ribosomal RNA (Nicolás and Castro, ; Chopra and Roberts, ). But, contrary to oxytetracycline, both horminone, several royleanones (Gaspar‐Marques et al ., ; Tada and Ishimaru, ; Yang et al ., ) and derivatives 2–12 are predominantly active against Gram‐positive bacteria. This may be a consequence of the differences on bacterial cell walls.…”
Section: Resultsmentioning
confidence: 99%
“…We planned to obtain catechol 7 from phenol 8 by Tada's method using m-chlorobenzoyl peroxide (mCBPO). 6 Phenol 8 would be synthesized from (−)-abietic acid (5) through allylic oxidation to 9, followed by aromatization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The ortho-oxidation of phenol 8 with m-chlorobenzoyl peroxide (mCBPO) 6 Because compound 6 is unstable and acid sensitive, 9 no acidic conditions could be applied during subsequent esterification and deprotection steps. Only Shiina reagent proved successful for the esterification of 6, although other condensation reagents, such as DCC, EDCI, and the use of pentafluorophenyl ester, did not produce the desired ester.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation